2017
DOI: 10.1017/s0033291717000186
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and circadian rhythm disturbance in bipolar disorder

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 39 publications
4
82
0
Order By: Relevance
“…Sleep disturbances have also been reported to be frequent in the euthymic state . Past studies have demonstrated that the sleep disturbances in the euthymic state included not only insomnia but also sleep–wake rhythm disorders, especially delayed sleep–wake phase disorders, suggesting that circadian rhythm dysfunction could be involved in the pathophysiology of BD. Pinho et al .…”
Section: Circadian Rhythm Markers In Bdmentioning
confidence: 99%
“…Sleep disturbances have also been reported to be frequent in the euthymic state . Past studies have demonstrated that the sleep disturbances in the euthymic state included not only insomnia but also sleep–wake rhythm disorders, especially delayed sleep–wake phase disorders, suggesting that circadian rhythm dysfunction could be involved in the pathophysiology of BD. Pinho et al .…”
Section: Circadian Rhythm Markers In Bdmentioning
confidence: 99%
“…There is considerable evidence of circadian rhythm dysfunction in patients with bipolar disorder including disturbances in the sleep/wake cycle, activity patterns, melatonin secretion, as well as suggestive associations with clock gene polymorphisms and epigenetic alterations . Clinical symptoms that are frequently reported include sleep timing disturbances , irregular daily schedules , and an evening preference .…”
Section: Introductionmentioning
confidence: 99%
“…At least three possible explanations may be worth considering in regards to the link between BD and the risk of OSA: Different types of sleep disturbance are described in all phases of BD, including remission . Sympathetic hyperactivity and hyperarousal states associated with sleep disturbance may lead to instability of the upper respiratory tract, which may contribute to subsequent OSA …”
Section: Discussionmentioning
confidence: 99%
“…• Different types of sleep disturbance are described in all phases of BD, including remission. 13 Sympathetic hyperactivity and hyperarousal states associated with sleep disturbance may lead to instability of the upper respiratory tract, which may contribute to subsequent OSA. 14 • Benzodiazepines, which have a sedative effect, are therefore prescribed to relieve these sleep problems.…”
Section: Discussionmentioning
confidence: 99%